Caribbean small island developing states (SIDS) experiences. Vol. 1 (UNDP. Regional Service Centre - LAC Port of SpainTT, 2010)
Highlights Caribbean small island developing states experiences. Involves effforts from national and local government, UNDP country offices and regional institutions.
Keywords: SMALL STATES